Child Learning with a Peer During the Implementation of Development Tasks - Jolanta Andrzejewska; Sabina Guz (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction: The student's activity in certain places and during well-thought developmental and didactic tasks is a factor that influences the process of learning,  upbringing and the way they initiate interactions with peers and teachers. Research Aim: This article attempts to present the unused potential of the pedagogy of place and the role of developmental and didactic tasks in the process of creation of the relations among students. Method: The material comprises two parts: the description of the educational project "Outside the Threshold"  that took the shape of the teaching experiment and the presentation of the results of the research. Results: The essence of this educational project was to develop students' key competences through developmental and didactic tasks in four-person peer groups"Conduit pipe". The research was aimed to find answers to the following questions: In what way the developmental and didactic tasks and educational situations promote the authentic students' cooperation. Conclusion: The analysis of the collected research material indicates the aspects that may constitute the basis for a wider discussion and for identifying some issues for further research, as well as for the improvement of mindfulness development in educational practice.